John Edward Bruce : Politician, Journalist, and Self-Trained Historian of the African Diaspora. - Crowder, Ralph L. (NYU Press, 2004)
John Edward Bruce, a premier black journalist from the late 1800's until his death in 1924, was a vital force in the popularization of African American history. "Bruce Grit," as he was called, wrote for such publications as Marcus Garvey's nationalist newspaper, The Negro World, and McGirt's Magazine. Born a slave in Maryland in 1856, Bruce gained his freedom by joining a regiment of Union soldiers passing through on their way to Washington, DC. Bruce was in contact with major figures in African American history, including Henry Highland Garnett and Martin Delany, both instrumental i.